Pengaruh Pengembangan Sumber Daya Manusia Terhadap Kinerja Tim Proyek Di Kontraktor Konstruksi - Ahmad Zacky Nasution; Syafika Syafika; Rinalia Fauziah Br Manik; Syarifah Khalisa Adilla (Journal of Innovative and Creativity, 2025)
The construction industry plays a vital role in infrastructure development and economic growth but faces high complexity in managing time, cost, and quality. Project success largely depends on human resources (HR) and the development of their competencies. Human resource development (HRD) includes technical training, managerial skill enhancement, and career coaching to improve effectiveness, motivation, and loyalty. Without continuous HRD, team performance declines due to limited skills and poor communication. This study analyzes the impact of HRD on project team performance in construction companies using a descriptive qualitative approach through literature review. The findings show that HRD enhances competence, coordination, motivation, and overall project performance. HRD should be seen as a long-term investment that boosts productivity, strengthens teamwork, and ensures sustainable project success.